Detecting implied scenarios in message sequence chart specifications. - Uchitel, Sebastian
Scenario-based specifications such as Message Sequence Charts (MSCs) are becoming increasingly popular as part of a requirements specification. Scenario describe how system components, the environment and users work concurrently and interact in order to provide system level functionality. Each scenario is a partial story which, when combined with other scenarios, should conform to provide a complete system description. However, although it is possible to build a set of components such that each component behaves in accordance with the set of scenarios, their composition may not provide the required system behaviour. Implied scenarios may appear as a result of unexpected component interaction. In this paper, we present an algorithm that builds a labelled transition system (LTS) behaviour model that describes the closest possible implementation for a specification based on basic and high-level MSCs. We also present a technique for detecting and providing feedback on the existence of implied scenarios. We have integrated these procedures into the Labelled Transition System Analyser (LTSA), which allows for model checking and animation of the behaviour model.
Keywords: Software; Software engineering; Requirements / Specifications; Languages; Tools; Computing methodologies; Simulation and modeling; Model validation and analysis; Algorithms; Languages; Verification; FSP; LTSA; Implementability; Labelled transition systems; Message sequence charts; Sythesis